Abdominal Migraine in a Eight year old Girl (Journal of Dhaka National Medical College & Hospital, 2017)
Abdominal migraine is a migraine variant, causing chronic idiopathic recurrent abdominal pain in 4-15% of children. It is usually seen between the ages of seven to twelve years and is more common in girls, with prevalence at the age of ten years. International Classification of Headache Disorders- (ICHD-2) defines Abdominal Migraine (AM) as idiopathic disorder characterized by attacks of midline, moderate to severe abdominal pain lasting 1-72 hours with vasomotor symptoms, nausea and vomiting, and included Abdominal migraine among the periodic syndromes of childhood that are precursors for migraine. A 8 years old girl was admitted in Dhaka National Medical College Hospital (DNMCH) with the complains of episodes of severe abdominal pain since five years of her age. The pain was associated with nausea and vomiting which lasted for two to three days. It was dull aching, predominantly around the umbilicus, usually in the evening, intermittent, getting relieved by taking painkillers and antacids or H2 blockers. For this reason she was admitted in different hospitals several times and usually interferes her normal daily activities but with periods of wellness between episodes. Her mother had history of headache since her childhood. On examination, she was pale and mildly dehydrated investigations were done such as CBC with film, Urine R/E, Serum electrolytes, LFT, RFT, Stool R/E, USG of Whole abdomen to exclude any pathology but nothing significant was found. She was treated with H2 blocker, antispasmodic, antiemetic and IV fluids and symptom subsided. Little evidence exists the use of drugs to manage AM. For acute treatment of attacks, there is no data regarding ibuprofen or acetaminophen, the 2 agent for which controlled data exist for migraine with- out aura in young children. There are likewise no data regarding the use of tryptans for AM. Preven- tive medications that have demonstrated efficacy in clinical trials include pizotifen, propranolol, and cyproheptadine for prevention of recurrent attacksJ. Dhaka National Med. Coll. Hos. 2017; 23 (01): 51-53